Effect of Denture Base Material on The Stresses Induced on Implant Supporting Mandibular Bar - retained Over-denture - Mohamed El Maroush (AlQalam Journal of Medical and Applied Sciences, 2025)
The aim of this study was to evaluate and compare the effect of heat cured acrylic resin denture base and glass fiber reinforced denture base on stresses induced on mandibular implant overdenture supporting structures by bar attachment using strain gauge analysis. Mandibular overdenture supported by a rigid interconnecting bar retained attachment connecting the two implants was constructed. According to the denture base material, mandibular overdentures were classified into Group I: Mandibular implant- supported overdenture was constructed using heat cured acrylic resin. Group II: Mandibular implant- supported overdenture was constructed using fiber reinforced acrylic resin. Two strain gauges were installed at the distal aspects of the implant to record the strain induced by anterior, unilateral and bilateral posterior loading of each overdenture using universal testing machine. Data was collected, tabulated and statistically analyzed. The result of this study showed that the highest stresses on the implant were recorded for the conventional heat cured acrylic denture base, and the difference was found to be statistically significant P<0.05 for both anterior and unilateral load. Within the limitation of this in vitro study, the use of fiber reinforced acrylic resin denture base material for implant supported overdenture leads to better stress distribution to the implant supporting bar attachment. هدف هذه الدراسة هو تقييم ومقارنة تأثير قاعدة طقم الأسنان المصنوع من راتنج الأكريليك المعالج بالحرارة وقاعدة طقم الأسنان المقوى بألياف الزجاج على الإجهادات الناجمة عن هياكل دعم طقم الأسنان فوق الغرسة السفلية عن طريق تثبيت القضيب باستخدام تحليل مقياس الانفعال. تم تصنيع طقم الأسنان فوق الغرسة السفلية المدعوم بقضيب ربط صلب مثبت يربط بين الغرستين. وفقًا لمادة قاعدة طقم الأسنان، تم تصنيف أطقم الأسنان فوق الغرسة السفلية إلى المجموعة الأولى: تم تصنيع طقم الأسنان فوق الغرسة السفلي المدعوم بالغرسة السفلية باستخدام راتنج الأكريليك المعالج بالحرارة. المجموعة الثانية: تم تصنيع طقم الأسنان فوق الغرسة السفلي المدعوم بالغرسة السفلية باستخدام راتنج الأكريليك المقوى بالألياف. تم تركيب مقياسين للانفعال على الجوانب البعيدة للغرسة لتسجيل الإجهاد الناتج عن التحميل الأمامي والأحادي الجانب والثنائي الجانب الخلفي لكل طقم أسنان فوقي باستخدام آلة اختبار عالمية. تم جمع البيانات وجدولتها وتحليلها إحصائيًا. أظهرت نتائج هذه الدراسة أن أعلى الضغوط على الغرسة تم تسجيلها لقاعدة طقم الأسنان الأكريليكي التقليدية المعالجة بالحرارة، ووجد أن الفرق كان ذا دلالة إحصائية P<0.05 لكل من الحمل الأمامي والأحادي الجانب. ضمن حدود هذه الدراسة المختبرية، فإن استخدام مادة قاعدة طقم الأسنان الأكريليكي المقواة بالألياف لطقم الأسنان المدعوم بالغرسة يؤدي إلى توزيع أفضل للضغوط على مرفق قضيب دعم الغرسة